MANAJEMEN PEMELIHARAAN FASILITAS BANGUNAN GEDUNG PADA PROYEK SWASTA: STUDI KASUS - Sholeh, Moh Nur; Malelak, Erastus Jimmy (Civil Infrastructure Engineering and Architectural Design, 2019)
The phase of buildings maintenance in the project life cycle is still not well structured when compared to construction phase, especially in government buildings. In contrast to private buildings that have been well managed in their care. This is due to the different funding patterns and budgets and the different division of responsibilities, the private sector is easier without a long flow when they want to maintain and finance the building. The purpose of this study is to review the management of maintenance of building facilities on private projects to be recommended to government-owned buildings. Case studies were carried out on one of the private-owned buildings in Central Java by taking a review of the diesel pump facilities. The research method is by observing the process of maintaining a diesel pump that is deepened by interviews and looking at the Standard Operational Procedure (SOP). The results showed that the One Point Lesson (OPL) maintenance system through daily, weekly, monthly, and annual maintenance on private buildings was quite effective. Maintenance is categorized as autonomous, corrective, and preventive maintenance. This maintenance system has the potential to be adopted into government buildings by carrying out more in-depth analysis.